Peran Media Sosial Instagram dalam Meningkatkan Daya Saing Coffee Shop di Medan Kota - Harahap, Nilfaujia; Nursaimatussaddiya, Nursaimatussaddiya; Pepriaman, Dedi (STIE Bina Karya, 2025)
The development of information and communication technology has brought significant transformation to business marketing strategies, including in the culinary sector. Instagram has become one of the most effective social media platforms for building interaction between business owners and consumers through visual strength and two-way communication. This study aims to analyze the role of Instagram in enhancing the competitiveness of coffee shops in Medan City. The research employed a qualitative descriptive approach using purposive sampling, involving coffee shop owners and managers who actively use Instagram as a promotional medium. Data were collected through in-depth interviews, observation, and digital documentation. The findings reveal that Instagram plays an essential role in strengthening business competitiveness through three main aspects: brand image development, customer engagement enhancement, and adaptation to digital trends. The use of features such as Stories, Reels, and Live has proven effective in attracting consumer attention, expanding market reach, and building customer loyalty. Therefore, Instagram serves not only as a promotional platform but also as a strategic instrument in developing competitive advantage for coffee shops in the digital marketing era.